Pembangkangan Hukum: Menakar Kepatuhan Organisasi Advokat Terhadap Putusan Hakim Yang Telah Berkekuatan Hukum Tetap - Susanto; Nurhayati; Dadan Herdiana (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2023)
The split within the Indonesian Advocates Association led to a dispute with its splinter organization, the Indonesian Advocates Association. The two have similarities in the use of the PERADIN brand, which has led to lawsuits in court. This research was conducted to determine the compliance of the Advocate Organization under the name Indonesian Advocates Association with a court decision that has permanent legal force related to the PERADIN organization brand dispute. The method used is qualitative normative research with a statutory approach in relation to the problems in this research. The results showed that the Indonesian Advocates Association illegally used the PERADIN Mark belonging to the Indonesian Advocates Association and the decision had permanent legal force. Even though there has been a decision with permanent legal force, the Indonesian Advocates Association did not voluntarily carry out the contents of the decision and even filed 5 (five) other lawsuits.